Effectiveness of Teaching Games for Understanding (TGfU): Using a modified Kasti game to stimulate elementary school students’ motor skills - Gustian, Uray; Gandasari, Fatima Maharani; Mahendra, Agus (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background Problems: Teaching Games for Understanding (TGfU) is still a challenge for Physical Education (PE) teachers. Teachers are still weak in applying the concept of TGfU to learning and lacking in improving motor skills, so it requires a study to apply the model of TGfU based on the characteristics of the school, the abilities of the students, and the ease of application by the teacher. Research Objectives: The study aims to test the use of the TGfU model using Kasti games to stimulate elementary school students' motor skills. Methods: The research design uses pre-expression with one-group pretest and posttest designs involving 24 students. The experiment implemented field games modified according to the TGfU's concepts and steps. The experiment conducted five meetings with a duration of 80 minutes each. Data collection was done using the Test of Gross Motor Development-2 (TGMD-2) and analysed using descriptive, quantitative, and different tests. Findings/Results: Based on the results of the statistical analysis, it shows that there has been a significant increase in students’ motor skills stimulated by applying learning with the TGfU model and using the Kasti game. Conclusion: The implementation of the TGfU model with the Kasti game approach can be used as an approach to stimulate students' motor skills. Further studies are needed to enhance the potential of TGfU in encouraging teachers to organise PE teaching according to the implemented curriculum, with the aim of encouraging students to actively participate in sports and learn motor skills.